Pengaruh Hedonic Shopping Motivation, Shopping Lifestyle dan Brand Trust terhadap Perilaku Impulse Buying Product Apple oleh Gen Z di Lamongan - Syifa’tul Nur Azizah; Indira Shofia Maulida (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
The use of Apple products among Generation Z is increasingly widespread today, especially the iPhone. Generation Z in particular prioritizes prestige as their lifestyle. This study aims to determine (1) the influence of hedonic shopping motivation, shopping lifestyle and brand trust partially on impulse buying behavior of Apple products by Gen Z in Lamongan. (2) the influence of hedonic shopping motivation, shopping lifestyle and brand trust simultaneously. (3) the influence of hedonic shopping motivation, shopping lifestyle and brand trust is most dominant on impulse buying behavior of Apple products by Gen Z in Lamongan.This study uses a quantitative research method with a sample size of 97 respondents. The data analysis methods used are validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination test, t test and f test. The results of this study indicate that partially there is a significant positive influence between the variables of hedonic shopping motivation, shopping lifestyle and brand trust on the impulse buying behavior of Apple products by Gen Z in Lamongan of t count> t table (t count X1 = 5.635, X2 = 3.720, X3 = 3.553> t table = 1.986). Simultaneously there is a significant positive influence between the variables of hedonic shopping motivation, shopping lifestyle and brand trust on the impulse buying behavior of Apple products by Gen Z in Lamongan of f count (87.648)> f table (2.70). The hedonic shopping motivation variable has the most dominant influence of (X1) = 0.414 on the Impulse Buying behavior of Apple products by Gen Z in Lamongan compared to the shopping lifestyle and brand trust variables.